Kentsel Açık Mekân Olarak Meydanların Yaşam Kalitesine Etkileri: Trabzon Örneği / The Effects of the Places as Urban Open Spaces on the Quality of Life: The Case of Trabzon - Bayramoğlu, Elif; Yurdakul, Nazlı Mine (Journal of History Culture and Art Research, 2019)
Abstract The rate of technological improvements, scientific activities and post-urbanization has increased rapidly, which has affected urban users. By creating an integral part of the city's environment, the use of active green areas enables the community to realize all sorts of social activities. City users prefer open public spaces in urban squares to perform recreational activities (relaxation, rest, eating and having a good time). Urban areas, which are mostly used by the users during the urbanization period, are the squares and the connected roads. The streets providing the plazas and transportation are the cultural heritage bearers of urban life as well as the memories that a city has accumulated over the years. The squares also have the effect of creating an image of the city reflecting its identity. As part of life in urban squares and streets, people are engaged in activities both physically and socially. However, these areas are occupied with heavy traffic and surrounded by the buildings at the point we are nowadays. For this reason, contemporary cities have begun to face contradictions as unidentified and unqualified compared to past cities. In this study, the city square and the connected Gazipaşa Street, Uzun Sokak, Maraş Street, which are described as the Trabzon Ataturk Field, were discussed in terms of square images, square functions, square functions and spatial structures. In this sense, the effects of the squares that differ from social, cultural and economical in terms of urban life, design and planning criteria have been evaluated. Observations and evaluations were carried out in the study. In this context, the quality of life of users has been evaluated and recommendations have been developed. Öz Teknolojik gelişmelerle bilimsel etkinlikler sonucu kentleşme oranı hızla artmış, bu durum kent kullanıcılarını etkilemiştir. Kent çevresiyle bir bütün oluşturarak aktif yeşil alan kullanımları ile toplumun her türlü sosyal aktiviteyi gerçekleştirebileceği olanaklara imkân sağlar. Kent kullanıcıları ise rekreatif (rahatlama, dinlenme, yemek yeme ve hoş vakit geçirme) etkinlikleri gerçekleştirmek için kent meydanlarındaki açık kamusal mekanları tercih ederler. Kentleşme süresi içerisinde kullanıcıların en yoğun kullandıkları kentsel alanlar meydanlar ve bağlantılı olan caddelerdir. Meydanlar ve ulaşımı sağlayan sokaklar bir kentin yıllar boyunca içinde biriktirdiği anıları ile kentsel yaşam noktası niteliğindeki kültürel bir miras taşıyıcılarıdır. Meydanlar aynı zamanda kimliğini yansıtarak kente imaj yaratma etkisi de vardır. Kent meydanları ve sokaklarda yaşamın bir parçası olarak insanlar fiziksel ve sosyal açıdan etkinliklerde bulunurlar. Ancak günümüzde geldiğimiz noktada bu alanlar yoğun trafik ile işgal edilerek binalarla kuşatılmıştır. Bu nedenle geçmiş kentlerine oranla günümüz kentleri kimliksiz ve niteliksiz olarak karşımıza çıkmaya başlamıştır. Bu çalışmada Trabzon Atatürk Alanı olarak nitelendirilen kent meydanı ve bağlantılı Gazipaşa Caddesi, Uzun Sokak, Maraş Caddesi’nde yapılar, meydan imgeleri, meydan işlev-fonksiyonları ve mekansal yapıları bakımından ele alınmıştır. Bu anlamda sosyal, kültürel ve ekonomik açıdan farklılık gösteren meydanların kent yaşamına olan etkileri, tasarım ve planlama kriterleri değerlendirilmiştir. Çalışmada gözlemler ve değerlendirmeler yapılmıştır. Bu kapsamda kullanıcıların yaşam kaliteleri değerlendirilerek öneriler geliştirilmiştir.